2021
DOI: 10.1177/0960327121991904
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA ploidy and micronucleus frequency in chronic smokers and impact of smoking cessation

Abstract: Tobacco use may initiate the process of oral carcinogenesis with clinically undetectable changes. Smoking cessation may prevent its progression. The objective of this study was to evaluate the association between DNA ploidy and micronucleus (MN) frequency in chronic smokers. Three groups were evaluated: Smoker Group, Former Smoker Group and Control Group. Exfoliative cytology was performed on the lateral border of the tongue and mouth floor. MN and DNA ploidy analyses were performed, as well as the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The latter are extracellular cytoplasmic bodies that are formed during anaphase from chromosomal fragments. Several studies showed that there is a correlation between the frequency of MN and severity of the genotoxic damage, these being further used for grading the lesion [26,27]. Therefore, MN count is regarded as an indicator of chromosomal aberrations and is useful in detecting early-stage carcinogenesis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The latter are extracellular cytoplasmic bodies that are formed during anaphase from chromosomal fragments. Several studies showed that there is a correlation between the frequency of MN and severity of the genotoxic damage, these being further used for grading the lesion [26,27]. Therefore, MN count is regarded as an indicator of chromosomal aberrations and is useful in detecting early-stage carcinogenesis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We read the manuscript recently published by Cruz et al 1 in the Human and Experimental Toxicology titled "Association between DNA ploidy and micronucleus frequency in chronic smokers and impact of smoking cessation" with much interest. In this article, the authors detected high frequencies of micronucleated cells in chronic smokers when compared to control group.…”
mentioning
confidence: 99%